Haemoproteus nucleocondensus n. sp. (Haemosporida, Haemoproteidae) from a Eurasian sogbird, the Great Reed Warbler Acrocephalus arundinaceus - Križanauskienė, Asta; Iezhova, Tatjana A.; Palinauskas, Vaidas; Chernetsov, Nikita; Valkiūnas, Gediminas (Zootaxa, 2012)
Haemoproteus (Parahaemoproteus) nucleocondensus n. sp. (Haemosporida, Haemoproteidae) is described from aEurasian songbird, the Great Reed Warbler Acrocephalus arundinaceus based on the morphology of its blood stages andpartial sequences of the mitochondrial cytochrome b gene. Transmission of this haemoproteid occurs in Africa, where theGreat Reed Warblers are infected. Due to unclear reasons, its transmission does not occur at European breeding groundsof this bird, resulting in absence of the parasites in juvenile birds before and during seasonal migration. Haemoproteusnucleocondensus can be readily distinguished from other avian haemoproteids by tiny, compact microgametocyte nucleithat are significantly smaller than macrogametocyte nuclei, a rare character of haemosporidian parasites. By thismorphological feature, the new species is similar to Haemoproteus payevskyi, Haemoproteus micronuclearis, andHaemoproteus nucleofascialis. Haemoproteus nucleocondensus can be readily distinguished from both H. payevskyi andH. micronuclearis, primarily due to its numerous growing gametocytes (size greater than erythrocyte nuclei), which donot touch the envelope of erythrocytes along their entire margin; such gametocytes do not develop in Haemoproteuspayevskyi and H. micronuclearis, but present in H. nucleofascialis. However, microgametocyte nuclei are band-like inshape in the latter parasite; that is not a case in H. nucleocondensus. Illustrations of blood stages of the new species aregiven, and morphological and phylogenetic analyses identify the DNA lineages that are associated with these parasites.Genetic distance between cyt b gene sequences of the new species and H. payevskyi, H. micronuclearis, and H.nucleofascialis is 4.4%, 5.9%, and 8.1%, respectively. Cytochrome b gene sequences (GenBank no. JX026901) can be used for bar-coding in studies of H. nucleocondensus.